Gold Nanorods for application in Plasmonic Luminescent Solar Concentrators - Mc Cormack, Sarah; Sethi, Arunima; Ahmed, Hind; Chandra, Subhash (My University, 2017)
Luminescent solar concentrator (LSC) device is based on energy down shifting phenomenon with a primary goal of trapping, and concentrating solar radiation. The trapped light is guided to the photovoltaic cell through total internal reflation where it is absorbed and converted to electricity. LSC with its flexible design have the potential to find extensive use in the building integrated photovoltaics [1]. However, the optical efficiency of LSCs is limited by the properties of doped fluorescent materials. Plasmonic properties of metal nanoparticles (MNP) such as Gold (Au) and nanorods can be used for the enhancement of fluorescence of quantum dots (QDs), rare earth complexes and organic dyes in LSC devices [2]. The fluorescence enhancement of the luminescent species placed in the vicinity of MNP is dependent on spacing between the fluorophore- MNP, surface plasmon resonance (SPR) spectral overlap, and orientation. To maximize plasmonic coupling it is required to control spacing with the fluorophores and that can be achieved through concentration distribution of MNPs. The MNP-fluorophore composite in a polymer matrix material is required to have soluble and dispersion compatibility in this matrix material. Since, the wide range of MNPs synthesised using wet chemistry are functionalized with CTAB (hexadecyltrimethylammonium bromide) [3, 4, 5], that is insoluble in organic solvent hence in the polymer. This requires functionalizing MNPs and to make them soluble in organic solvent and polymer. Nanorods (NRs) were synthesized using the seed mediated wet chemical process, with the capping agent. The colloidal solution obtained has a high shape yield for the NRs as is evident by UV-VIS and SEM characterisation. The NRs were successfully separated from the by-products such as spheres and cubes.
PUBLISHED
Keywords: Plasmodic coupling; Luminiscent solar concentrators; Gold nanorods